The Role of Social Guidance on Poverty Elevation Program A Study on Social Guidance of Business Group(Kube) for the Poors in Banjarmasin Municipality - Lidia Nugrahaningsih Ayal (Balai Besar Penelitian dan Pengembangan Pelayanan Kesejahteraan Sosial, Kementerian Sosial, 2015)
Social guide is supporting factor for the success of people with social welfare problem handling. This research is meant to know the role of social guidance on business group (Kube) program) and its supporting and handicap factors. Research location is determined purposively in Banjarmasin Municipality, based on the consideration that in Banjarmasin found Kube program almost in every district. Data are analyzed through qualitative-descriptive technique. The research finds that social guidance has a significant role in supporting the development and success of poverty handling through Kube program in Banjarmasin Municipality. It is recommended that the Ministry of Social Affairs through Board of Training and Education of Social Welfare to upgrade the ability of social guides through education and training so that they can work professionally, oversee and facilitate social guides so that Kube runs optimum. It is hoped that social guides create network with related agencies, like social agency, work training board, industry, business, and cooperation agency.